Compression‐only CPR training in elementary schools and student attitude toward CPR. Issue 8 (13th April 2016) - Kitamura, Tetsuhisa; Nishiyama, Chika; Murakami, Yukiko; Yonezawa, Takahiro; Nakai, Shohei; Hamanishi, Masayoshi; Marukawa, Seishiro; Sakamoto, Tetsuya; Iwami, Taku
Abstract: Background: Little is known about the effectiveness of systematic cardiopulmonary resuscitation (CPR) training for elementary school children. Methods: We introduced systematic training of chest compression‐only CPR and automated external defibrillator (AED) use to elementary school students aged 10–12 years at 17 schools. The questionnaire compared student attitudes towards CPR and their knowledge about it before and after CPR training. We also evaluated parent and teacher views about CPR training in school education. The primary outcome was positive attitude, defined as "yes" and "maybe yes" on a 5 point Likert‐type scale of student attitudes towards CPR.1 Results: A total of 2047 elementary school students received CPR training. Of them, 1899 (92.8%) responded to the questionnaire regarding their attitude towards CPR before and after the training. Before training, 50.2% answered "yes" and 30.3% answered "maybe yes", to the question: "If someone suddenly collapses in front of you, can you do something such as check response or call emergency?" After training, their answers changed to 75.6% and 18.3% for "yes" and "maybe yes", respectively. Many of the students (72.3%, 271/370) who did not have a positive attitude before CPR training had a positive attitude after the training ( P  < 0.001). Most students understood how to perform CPR (97.7%) and use an AED (98.5%). Parents (96.2%, 1173/1220) and teachers (98.3%, 56/57) answered that it was "good" and "maybe good" for children to receive the training at elementary schools. Conclusion: Systematic chest compression‐only CPR training helped elementary school students to improve their attitude towards CPR.